Electrostática y EAO: una experiencia de simulación - Massons, J.; Camps, J.; Cabré, R.; Ruiz, X.; Díaz, F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
In this work the inclusion of educational software in the teaching of physics is analyzed. The program used corresponds to the computer simulation of electrostatic fields, and it was applied to students of first year of universitary level in a Faculty of Chemistry.